A cross-sectional survey of international voyage ships entering Zhoushan Port by sea, Zhoushan, 2020-2022 - Hua, Yuzhe; Dai, Yaxin; Yi, Jingping; Wu, Wenjie; Li, Peng; Li, Kefeng; Chen, Wei; Tang, An (Frontiers in Marine Science, 2025)
Crew members aboard international voyage ships are susceptible to imported acute respiratory infections, leading to clusters of outbreaks that pose challenges to the health of crew members. The aim of the proposed study was to optimize a plan for the quarantine process and rescue measures in response to a coronavirus disease 2019 (COVID-19) outbreak at sea to provide policy guidance for the prevention and control of severe infectious diseases on international voyage ships. Here, we described the baseline characteristics of international voyage ships and crew members entering Zhoushan Port from 2020 to 2022 and analyzed the factors influencing the incidence rate of COVID-19 among crew members. There were 161 COVID-19 cases among cargo ships entering Zhoushan Port by sea, with an average incidence rate of 16.00% (95% CI: 13.73%–18.27%). The incidence rate of COVID-19 was significantly higher among crew members with replacement, long voyage, and those who stayed at multiple anchorages or stayed for a long time. The risk of COVID-19 infection for crew members staying at more than 4 anchorage was the highest, which was 2.667 (95% CI: 1.857–3.830) times that of crew members staying at less than 4 anchorage. We developed and refined the workflow for a public health assistance plan for outbreaks at sea on the basis of our experience with several COVID-19 outbreaks on international voyage ships. The workflow includes fundamental requirements, sampling and testing methods, personnel transfer procedures, medical waste disposal guidelines, and disinfection procedures for affected ships. Our public health assistance plan can be applied to other international voyage ships for which urgent public health assistance is needed during sudden infectious disease outbreaks.